The Performance of the Solar Panel Installation Configuration in the Face of Lighting Changes - Asnil Asnil; Hanif Hazman (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Partial shadow is one of the factors that affect the efficiency of solar panels, besides temperature and humidity. Partial shade reduces the performance of the solar panel and gives rise to some local maximums. One effort to reduce the negative effects of this partial shade is to reconfigure the installation of solar panels. This study aims to examine the effect of partial shadows with various solar panel configurations. The 3x3 system was used in this study, with several configurations namely Series Parallel (SP), Total Cross Tied (TCT), Triple Tied (TT), Bridge Link (BL), and Honey Comb (HC). The test results are monitored through a Visual Basic-based interface that displays data in graphical form. The test results show that the configuration that produces the most energy is TCT followed by TT, BL, HC and SP which produces the lowest energy from all tests. Bayangan parsial merupakan salah satu faktor yang mempengaruhi efisiensi dari panel surya, disamping suhu dan kelembapan. Bayangan parsial membuat kinerja panel surya tidak maksimal dan menimbulkan beberapa titik maksimum lokal. Salah satu upaya untuk mengurangi efek negatif dari bayangan parsial ini adalah dengan melakukan rekonfigurasi pemasangan panel surya. Penelitian ini bertujuan untuk melihat pengaruh bayangan parsial dengan berbagai konfigurasi pemasangan panel surya. Sistem yang digunakan adalah 3x3 dengan konfigurasi Series Parallel (SP), Total Cross Tied (TCT), Triple Tied (TT), Bridge Link (BL), dan Honey Comb (HC). Hasil pengujian dimonitoring melalui interface berbasis Visual Basic yang menampilkan data dalam bentuk grafik. Hasil pengujian menunjukkan konfigurasi yang menghasilkan energi paling besar adalah TCT kemudian diikuti oleh TT, BL, HC dan SP menghasilkan energi yang paling rendah dari semua pengujian.